Dinamika Total Protein Serum Tikus Putih (Rattus novergicus) yang Diberi Mikrokapsul Imunoglobulin-G Anti-H5N1 (DYNAMICS OF TOTAL PROTEIN SERUM OF RATTUS NOVERGICUS GIVEN MICROCAPSULES OF IMMUNOGLOBULIN G ANTI H5N1) - Riwu Wolo, Kathirina Beatrik; Esfandiari, Anita; Murtini, Sri; Wulansari, Retno (Jurnal Veteriner; Vol 20 No 4 (2019)DO - 10.19087/jveteriner.2019.20.4.504, 2019)
Immunoglobulin G (IgG) from colostrum of hyperimmune colostrum obtained from vaccinated cattle with H5N1 vaccine is potential to be developed into passive immunotherapy product for “bird flu” infection. The administration of passive therapy can be done orally, but the environmental conditions of the digestive tract can cause IgG damage, so the microencapsulation technique was used in this study to protect IgG. This study aimed to evaluate the absobrption of H5N1 IgG anti-Avian Influenza which was microencapsulated using rats (Rattus novergicus) as animals model. This study was conducted using 108 adult male white rats (Rattus norvegicus), Wistar strain, approx. 250 grams of body weight. Rats were divided into three treatment groups (N = 36), i.e. control group (K) were given aqua distilled water, suspension group (S) were given anti-H5N1 IgG suspension, and microcapsules group (M) were given microcapsules equivalent to suspension with the titer of 25. Necropsy was carried out at four observation points (2, 4, 6 and 8 hours) to collected blood through the heart and collected in vacutainer without anticoagulants to obtain serum. The blood serum then analyzed for total protein and globulin and albumin/globulin ratio (A/ G). The results showed that the level of total protein and globulin group M was higher and significantly different (P> 0.05) compared to K and S at the end point of observation. The A/G ratio in group K showed a significant increase (P> 0.05) at the end point of observation while in group M there was a marked decrease (P> 0.05) at the time point of 2 hours to 4 hours and then constant until the end of observation. These results showed that administration of anti-H5N1 IgG microcapsules can increase total levels of protein and globulin in the blood.